Topological optimization design of the front coupling rod of prosthetic knee joint based on Inspire - Xiaofei Su; Yan Zhu; Hui Dong; Jingyu Yang; Lu Wang; Zhengyu Zhao (Journal of Engineering and Applied Science)
Abstract To enhance the movement efficiency and comfort of patients using prosthetic limbs, Altair Inspire software is employed to optimize the topology of the front coupling rod in the prosthetic knee joint motion mechanism, as well as the structure of its connecting parts. This optimization process is aimed at achieving mass reduction of the prosthetic motion mechanism while improving its structural performance. Based on the mathematical modeling method of variable density method, the motion analysis and initial strength analysis of the front coupling member are carried out, and the distribution of its displacement, safety factor, and Mises equivalent stress were obtained. Using different shape control and aiming at reaching the stiffness maximum, the topological optimization and fitting of the front coupling members were carried out several times with the mass and thickness degrees as design constraints, and then the optimal optimization model can be obtained. It has been proved that compared with the initial model, the weight of the final optimization model was reduced by 62.15%, which greatly solves the problem of material redundancy. Besides, all the indicators met the requirements of design strength, and the optimization effect was remarkable. Finally, 3D printing technology was used to print the pre-optimized and post-optimized model components. After specific tests, it can be concluded that the topology optimization design of the front coupling rod is realistic and reasonable.